Implementation Of Promotion Push Notifications in Ticket Booking Applications Using Forward Chaining Algorithm - Muhamad Fuat Asnawi; Aletha Dhelvya (Clean Energy and Smart Technology, 2022)
Waterfall is a leading tourist attraction in Winongsari Village, Kaliwiro District, Wonosobo Regency. This waterfall, named Curug Winong, has become a developing tourist spot. This research contains the design and development of promotion push notifications using the Forward Chaining method which is intended to help determine promotions. This application was developed using the PHP programming language with a MySQL database. This application determines the promotion with the conditions that have been determined. Based on dates, holidays, and other applicable conditions. system testing, namely black box and white box testing.